What Constitutes as Limitation of (Human) Rights in Indonesian Legal Context? - Jayadi, Anbar (Faculty of Law, Hasanuddin University, 2017)
This article reviews the interpretation of the Constitutional Court (the Court) on the Article 28J paragraph (2) of the 1945 Constitution by looking into the rulings related to the Information and Electronic Transaction Law. These rulings are chosen because, in those rulings, tensions between individual and public interest are apparent. For example, the tension between the right to privacy and freedom of expression, and the tensions between freedom of expression and public order. The rulings that will be studied in this writing are Ruling No. 50/PUU-VI/2008, Ruling No. 2/PUU-VII/2009, Ruling No. 5/PUU-VIII/2010, Ruling No. 52/PUU-XI/2013, and Ruling No. 20/PUU-XIV/2016. In studying those rulings, this article use a legal method namely the interpretation of arguments, e.g. what are the arguments provided by the claimants in the case in relation to the Article 28J paragraph (2) of the 1945 Constitution and how does the Court responds to such arguments. Additionally, this writing will also compare the rulings to each other to portray the â€œvarietyâ€ of interpretation by the Court over the time. Furthermore, this article will compare the Article 28J paragraph (2) of the 1945 Constitution and the Courtâ€™s interpretation of it to other standards of limitation in other human rights instruments such as European Convention on Human Rights (ECHR) and International Covenant on Civil and Political Rights (ICCPR) in order to depict what are the distinctive features of limitation of rights in Indonesian regime in comparison to other regimes. Last but not least, this article analyze what are the lesson learned from studying the Courtâ€™s interpretation and the possible consequence of such interpretation to the human rights protection in Indonesia.